MENINGKATKAN KETERAMPILAN MEMBUAT PALAI RINUAK MELALUI METODE LATIHAN PADA ANAK TUNAGRAHITA RINGAN - Eli Haryeti, Asep Ahmad Sopandi, Mega Iswari (Universitas Negeri Padang, 2013)
This research aim to: demonstrate the effectiveness of training methods in improving the skills of making palai rinuak for mild mental retardation children in the DV classes at State SDLB 64 Surabayo Lubuk Basung. This research use approach of Single Subject Reaserch (SSR) with A-B desain. Research subjects are children mild mental retardation